생물담체를 충진한 토양피복 산화접촉공정의 하수처리특성 - 김홍재(Hong Jae Kim); 강재희(Jae Hee Kang); 이기석(Ki Seok Lee); 강창민(Chang Min Kang); 정선용(Seon Yong Chung); Kubo Motoki (Daehan hwan'gyeong gonghag hoeji, 2005)
This study was performed to compare the treatment efficiencies of two media, newly developed Bio-rock and conventional gravel, in soil clothing contact oxidation process. The composition of synthetic wastewater were $COD_{Cr}$ $150{\sim}370\;mg/L$, $BOD_5$ $150{\sim}270\;mg/L$, T-N $20{\sim}60\;mg/L$, T-P $5{\sim}25\;mg/L$, pH 7 and 2 mL/L of trace element solution. The experiment using two reactors was comparatively conducted for the flow rate of 40 L/d for 13 months, respectively. Initially Bio-rock reactor was increased to pH 12 due to $Ca(OH)_2$ with hydration of cement, but gravel reactor was dropped to pH 4 due to the degradation of organic material and nitrification. This significant pH variation deteriorated the growth and activity of microorganism. But the high pH of Bio-rock seems favorite to ammonia stripping and precipitation of phosphate. Such pH variation of Bio-rock and gravel reactors were finally stabilized to pH 8 and pH 6, respectively. The removal efficiencies of organic compounds from Bio-rock reactor were 96% of $COD_{Cr}$, 98% of $BOD_5$, 80% of T-N and 85% of T-P which stably coping against variation of influent concentration. But those of gravel reactor were 96% of $COD_{Cr}$, 96% of $BOD_5$, 42% of T-N and 40% of T-P, respectively. The Bio-rock was 2 times higher than T-N and T-P in treatment efficiency. And electron-microscopic examination showed that Bio-rock was more favorable to microbial adherence than gravel. The microbial populations were $5.2{×}10^6\;CFU/mL$ of Bio-rock reactor compared to $2.6{×}10^6\;CFU/mL$ in gravel reactor. In result Bio-rock was favor to microbial adherence and high treatment efficiency in spite of variation of influent concentration which had the advantages in saving running time and reducing site requirement. 본 연구는 토양피복 접촉산화공정에서 새로 개발된 생물담체(Bio-rock)와 기존에 이용되어온 쇄석의 처리효율을 비교하기 위해 실시되었다 합성폐수는 $COD_{Cr}$ $150{\sim}370\;mg/L$, $BOD_5$ $150{\sim}270\;mg/L$, $T-N$ $20{\sim}60\;mg/L$, $T-P$ $5{\sim}25\;mg/L$, pH 7, 미량원소용액 2 mL/L로 조제되었다. 반응조는 2기를 준비하여 유입수량을 40 L/day로 하여 약 13개월간 운전했다. 초기 바이오락 반응기는 시멘트중의 $Ca(OH)_2$의 용출에 의해 pH 12까지 증가하였으나, 쇄석은 유기물 분해와 질산화에 의해 pH 4까지 감소하였다. pH의 불균형은 유기물 및 질소 분해균의 성장 및 활성에 저해를 초래했다 그러나 바이오락의 높은 pH는 암모니아 탈기와 인의 화학침전에는 유리한 것으로 판단되었다. 정상상태에서 바이오락은 $COD_{Cr}$ 96%, $BOD_5$ 98%, T-N 80%, T-P 85%의 높은 제거율을 나타내었고. 유입농도의 변화에도 매우 안정적이었다. 반면 쇄석의 경우 $COD_{Cr}$ 96%, $BOD_5$ 96%, T-N 42%, T-P 40%의 제거율을 나타내었다. 바이오락은 쇄석에 비해 질소, 인의 처리효율이 2배나 높았다. 또 전자현미경 분석결과에서 바이오락은 미생물의 부착이 쇄석에 비해 양호했고, 미생물 농도는 바이오락이 $5.2{×}10^6\;CFU/mL$, 쇄석이 $2.6{×}10^6\;CFU/mL$로 바이오락이 2배 높았다. 따라서 바이오락은 미생물 부착이 용이하고 처리효율이 높으며 유입농도 변동에도 안정적으로, 향후 처리기간 단축 및 부지면적의 감소에 유리하리라 판단된다.